PENGARUH KOMUNIKASI, PENDIDIKAN, DAN KOMPENSASI TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN SURUH INFLUENCE OF COMMUNICATION, EDUCATION, AND COMPENSATION ON VILLAGE DEVICES PERFORMANCE IN SURUH SUB-DISTRICT - Desti Lestari; Sri Rahayu; Nurmiyati Nurmiyati (BISECER (Business Economic Entrepreneurship), 2022)
In the village administration, village officials are assigned to provide good services to the government and the interests of the local community in the government system, however the reality is that the performance or quality of service provided by village officials in the Subdistrict is low and this is often complained by local residents because they are slow and not responsive in serving the community. The factors that affect performance are communication, education, and compensation. The purpose of this study was to determine the effect of communication, education, and compensation on the performance of village officials in Suruh District.The population in this study were all village officials in Suruh District, amounting to 249 people with a sample of 153 which was calculated using the Slovin formula. The technique of collecting the sample is proportionate stratified random sampling, which is done with the education strata of SD, SMP, SMA. Communication, education, and compensation together have an influence on the performance of village officials with the correlation coefficient for communication of 0.617, for education of 0.587 and compensation of 0.521, which if interpreted the tendency is included in the medium category. In addition, communication, education and compensation have an influence on the performance of village officials indicated by the regression coefficient for communication of 0.304, for education the regression coefficient is 0.279 and the compensation regression coefficient is 0.287. The effect of communication, education, and compensation jointly affects the performance of village apparatus in Suruh District as shown in the results of the determination test of 55.9% with a calculated F value of 65.169 which is greater than F table 2.67 and a significance value of 0.000 which smaller than the significance level of 0.05.